Antimicrobial activity and phytochemical screening of ananas nanus (dwarf pineapple) extracts / Faaizun Asyikin Sahmenan - Sahmenan, Faaizun Asyikin (Faculty of Applied Sciences, 2017)
For so many years, multiple resistances in human pathogenic microorganism have increased due to unselective used of antibiotic drugs in order to treat infectious diseases. The objectives of present study were to determine the phytochemical compounds of Ananas nanus by performing phytochemical screening test using methanol and hexane and to determine the antimicrobial activity of Ananas nanus against pathogens such as Staphylococcus aureus, Escherichia coli and Klebsiella pneumonia. Phytochemical screening showed presence of terpenoids, alkaloids and Quinones for both leaf and fruit of Ananas nanus while glycosides only present in the fruit. Antimicrobial activity was done by using disc diffusion method with different types of concentrations and solvent. Methanolic extracts produced inhibition zones in all concentrations and the higher number of concentration, the larger the inhibition zone, while hexane extract gave negative result for all concentrations. The antimicrobial activity of standard antibiotic gentamycin was studied in comparison with the leaf extraction. The ability of the crude leaf extract of Ananas nanus to inhibit the growth of bacteria was an indication that this species may have antimicrobial potential that can be engaged in the management of microbial infections.